Hemostatic Activity of Canine Never-Frozen Liquid Plasma Collected for Transfusion - Proverbio, Daniela; Perego, Roberta; Baggiani, Luciana; Spada, Eva (Frontiers in Veterinary Science, 2022)
This study measured the changes of hemostatic activity in liquid plasma (LP) over 7 days of storage. Five canine plasma units, divided into two aliquots were evaluated: one stored refrigerated at 2–6°C as never-frozen LP and one frozen at −18°C as fresh frozen plasma (FFP). Clotting times, coagulation activities of factor (F) V, VIII, X, XI, antithrombin (AT), and von Willebrand (vWF), fibrinogen and D-dimers (DD) content were assessed before storage (baseline value), and after 12, 24, 48 h and 7 days (D7) in LP stored refrigerated, and on day 7 in FFP. At baseline median values of all factor activity were greater than 80%, and for clotting times, AT, fibrinogen and DD content, were within the canine reference range. Some hemostatic parameters changed significantly over 7 days and at the end of storage in LP. However, median activities of FV, FVIII, FX and FXI, coagulation time, AT, fibrinogen and DD content remained within reference ranges at all time points. The only exception was for vWF which median activity was lower than reference range for all storage time points. Activity of FVIII was significant lower in LP at D7 when compared to activity in FFP, with values of 62 vs. 118%, respectively. DD content showed a median value higher than reference range in FFP at D7. Despite some statistically significant changes at the end of 7-day storage period, never-frozen LP maintained median factor activities >80% for most factors. The clinical impact of the drop over time of vWF activity is unknown.